2012
DOI: 10.1111/j.1442-200x.2012.03646.x
|View full text |Cite
|
Sign up to set email alerts
|

Paramyotonia congenita: From clinical diagnosis to in silico protein modeling analysis

Abstract: Diagnostic physical interventions in the patient confirmed the phenotype presentation consistent with PMC, and the in silico protein modeling analysis of p.Arg1448His predicted structural changes which can affect function of the protein. All the data confirmed the diagnosis of PMC in the patient and added to existing literature emphasizing the important role of arginine residue at 1448.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…The R1448C mutation of SCN4A is commonly considered as the causative factor. This variant is consistent with epidemiological data from other countries [10] , [21] , [24] . According to previous studies, the most representative features of myotonia may be explained by the abnormal hyperexcitability of skeletal muscle induced by altered inactivation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The R1448C mutation of SCN4A is commonly considered as the causative factor. This variant is consistent with epidemiological data from other countries [10] , [21] , [24] . According to previous studies, the most representative features of myotonia may be explained by the abnormal hyperexcitability of skeletal muscle induced by altered inactivation.…”
Section: Discussionsupporting
confidence: 91%
“…Structurally, the protein has four homologous domains (DI, DII, DIII, and DIV), each of which consists of six transmembrane alpha-helical segments (S1, S2, S3, S4, S5, and S6). The S4 segment in each domain contains from four to seven repeated three-residue motifs of a positively charged amino acid (usually arginine) followed by two hydrophobic amino acids [21] . The high concentration of positive charges in this alpha-helical segment suggests that the S4 segment is involved in voltage-dependent gating [5] .…”
Section: Discussionmentioning
confidence: 99%
“…The mutation c.3938C>T (p.T1313M), which is the most frequently reported mutation in literature, was present in 2 of our families. This mutation is located in the DIII-DIV linker and is associated with classic characteristics of PMC: cold-and exercise-induced muscle stiffness as well as intermittent periods of weakness not necessarily related to cold or myotonia 12,13 . T1313 residue is located next to the COOHterminal end of the IFM motif, which is thought to serve as an inactivation particle that blocks the pore during fast inactivation 14 .…”
Section: Discussionmentioning
confidence: 99%
“…These mutations were associated with classic characteristics of PC: cold-and exercise-induced muscle stiffness as well as intermittent periods of weakness not necessarily related to cold or myotonia. 9,18,[41][42][43] Functional experiments have shown that the mutations R1448H and T1313M impairs fast inactivation of sodium channels in a temperature-sensitive model, which may help explain the clinical phenotype of patients with PC who have these mutations. 44 Family 10 possessed a novel deletion (c.2638_2640delAAG); both the proband and his mother had this mutation.…”
Section: Discussionmentioning
confidence: 99%
“…4 More than 100 mutations in CLCN1 have been linked to MC, and more than 50 mutations have been identified in the SCN4A gene, of which about 20 have been linked to PC. 5 Most of these studies were conducted outside China, raising the question of how relevant they are to Chinese patients with MC, SCM, and PC. Indeed, in Chinese populations, fewer than 20 mutations in CLCN1 have been associated with MC [6][7][8][9][10][11] and only 8 mutations in SCN4A have been associated with SCM or PC.…”
Section: Introductionmentioning
confidence: 99%